2018
DOI: 10.1111/tbed.13001
|View full text |Cite
|
Sign up to set email alerts
|

The rise of the rosette agent in Europe: An epidemiological enigma

Abstract: International biodiversity assessments often overlook the role of emerging infectious pathogens in the decline of freshwater fish populations despite the many examples of emerging diseases in other more visible taxa on a global scale. Whilst the introduction of the rosette agent Sphaerothecum destruens in Europe remained an epidemiological enigma, recent findings have shown that this parasite arrived in Europe with the introduction of the healthy carrier Pseudorasbora parva from China nearly 60 years ago and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Accordingly, Hardouin et al. (2018), and Combe and Gozlan (2018) suggested that the P. parva introduction into Iran might have originated from an unsampled population in the Korean Peninsula, which was missing in their studies. Our results highlight the presence of an undescribed lineage in the Korean Peninsula, separated from the lineage/lineages found in China by 13 fixed substitutions (3.1% sequence divergence).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, Hardouin et al. (2018), and Combe and Gozlan (2018) suggested that the P. parva introduction into Iran might have originated from an unsampled population in the Korean Peninsula, which was missing in their studies. Our results highlight the presence of an undescribed lineage in the Korean Peninsula, separated from the lineage/lineages found in China by 13 fixed substitutions (3.1% sequence divergence).…”
Section: Discussionmentioning
confidence: 98%
“…High densities of P. parva have severe and significant impacts on native trophic food webs, resulting in overlaps with native fishes trophic niche (Britton et al., 2010). Additional concerns include egg predation, hybridisation with endemic and rare species (Gozlan & Beyer, 2006; Konishi et al., 2003; Simon et al., 2011), facultative parasitism (Gozlan, Andreou, et al, 2010), and transmission of diseases such as the rosette agent Sphaerothecum destruens , which is a novel fungal fish pathogen responsible for the decline of many native fish populations (Andreou & Gozlan, 2016; Combe & Gozlan, 2018; Spikmans et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an indirect transmission cycle has been contemplated as well, given the generalist infectivity observed in T. philomaios and ichthyosporean parasites (Andreou et al 2012; Rowley et al 2013; Combe and Gozlan 2018). Copepods have been proposed as the missing intermediate host for the fish parasite I. hofferi , which infects herring and salmon species (Hershberger et al 2002; Gregg et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Also, some chronic diseases caused by fungal and fungal-like pathogens exhibit no visible clinical symptoms which make their presence harder to trace and increase the spread of these diseases. For example, by hitch-hiking an invasive fish species (Pseudorasbora parva) as the carrier, the rosette agent Sphareothecum destruens (Mysomycetozoa)a generalist parasite capable of infecting a wide range of hosts with varying severityis now spread across Europe and a threat to most local fish species (Combe & Gozlan 2018). Most works on fungal and fungal-like pathogens in marine species, however, focus on the development of detection methods and pathological descriptions (Mendonca & Arkush 2004;Andreou et al 2012), with minimal work focuses on pathogens' protein constituent and mechanism of infection.…”
Section: Fungal and Fungal-like Pathogensmentioning
confidence: 99%